The Effect of Initial Location Assignment on Healthcare Utilization of Refugees - Shobhit Kulshreshtha (Global Labor Organization (GLO), 2025)
Characteristics of a place, such as healthcare access and the local environment, influence healthcare utilization. Refugees resettled in developed countries are often assigned locations based on the host country's assignment policies, yet the impact of initial placement on their healthcare usage remains understudied. I use Dutch administrative data to examine the effect of conditions in the initial municipality on healthcare utilization of refugees, leveraging the random assignment of refugees. Being assigned to a municipality with a higher healthcare utilization as measured by depression medication usage, hospital visits, and general practitioner costs among non-refugees increases healthcare utilization of refugees. I provide suggestive evidence on possible mechanisms and find that local healthcare access and socio-economic status of the municipality play an important role in healthcare utilization of refugees. This study contributes to the ongoing policy debates on providing separate and more targeted healthcare services for the refugee population.
Keywords: J15; I15; I18; R23; 330; refugees; healthcare utilization; place effects; quasi-experiment